Texts Buried in Oblivion. Testimonies of Two Refugees from the Mass Grave at Poniatowa - Andrzej Żbikowski (Zagłada Żydów)
This article contains an analysis and extensive quotations from accounts of two Jewish women, the only survivors of prisoners' execution at the Poniatowa compulsory labour camp. This execution was part of a large-scale operation to physically liquidate Jewish prisoners, the so-called “Operation Harvest” (Erntefest), carried out in the first week of November 1943 at the camps in Trawniki, Poniatowa and Majdanek (in Lublin). Both women survivors,. Due to a number of coincidences, managed to get to Warsaw and, helped by the “˚egota” – Council to Aid the Jews, lived to see the liberation. In this article I also analyse the circumstances of both accounts, reasons for withholding their publication as early as war time, and the importance , for our knowledge, not only of the executions, but also for the nature of complicated Polish–Jewish relations during World War II, because it was the Poles' help that the fate of escaped prisoners hinged upon.